Leather-like pieces
The leather-like sheet with a specific resin layer composition addresses the issues of frictional melting and bending resistance, ensuring durability and appearance through controlled particle size and heat-resistant spherical particles.
Patent Information
- Application Number
- CN202080090249.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2020-12-03
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-12-03
AI Technical Summary
Leather-like sheets used in sports shoes are prone to melting due to friction heat and bending, lacking sufficient resistance to both frictional melting and bending.
A leather-like sheet comprising a fiber substrate, an intermediate resin layer, and a surface resin layer containing polyether polyurethane and spherical particles with specific heat resistance and particle size distribution, providing high resistance to frictional melting and bending.
The leather-like sheet achieves both high resistance to frictional melting and bending, with cracks forming after 300,000 cycles or more in bending tests, maintaining a balance of mechanical properties and appearance.
Smart Images

Figure CN114867907B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to leather-like sheets. Background Art
[0002] In the past, leather-like sheets such as artificial leather and synthetic leather were used as interior materials for shoes, clothing, vehicles, and furniture. Such leather-like sheets have uses where the surface is in contact with other objects. For such uses, the leather-like sheets are required to have the property of not being easily worn due to friction with other objects.
[0003] For example, the following Patent Document 1 discloses a leather-like sheet, wherein a resin skin layer mainly composed of a non-yellowing polycarbonate urethane resin is laminated on the surface of a natural leather substrate via an adhesive layer formed of a resin mainly composed of a polycarbonate urethane resin, and the leather-like sheet contains 3 to 50 parts by weight of spherical fine powder having an average particle size of 10 μm or less per 100 parts by weight of the resin mainly composed of the non-yellowing polycarbonate urethane resin. In addition, melamine resin, phenolic resin, and benzoguanamine resin are disclosed as the spherical fine powder.
[0004] For example, Patent Document 2 below discloses a ball cover material including a fiber base material and a surface resin layer disposed on one side of the fiber base material and containing a polymer elastic body, inorganic particles, and protein powder.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 7-150479
[0008] Patent Document 2: Japanese Patent Application Publication No. 2016-67666 Summary of the invention
[0009] Problems to be solved by the invention
[0010] For example, shoes used when playing sports in a gymnasium are repeatedly rubbed against the floor during competition, and the rubbed parts may melt due to friction heat. In addition, shoes used when playing sports in a gymnasium are repeatedly bent due to the activities of the athletes. Therefore, for shoes used when playing sports in a gymnasium, a leather-like sheet having a surface with high friction melting resistance that is not easily melted by friction heat and high bending resistance is sought.
[0011] An object of the present invention is to provide a leather-like sheet having a surface having both high resistance to frictional melting and high resistance to bending.
[0012] Solutions to the problem
[0013] One aspect of the present invention relates to a leather-like sheet comprising: a fiber substrate, an intermediate resin layer laminated on one side of the fiber substrate, and a surface resin layer laminated on the intermediate resin layer, wherein the surface resin layer contains polyether polyurethane and spherical particles having a heat resistance of 200° C., and the content of the spherical particles is 5 to 40% by mass, the specific heat of the spherical particles is 0.95 kJ / (kg·K) or more, and the particle size D at 50% by volume of the cumulative distribution is 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D 10 ≤3. According to such a leather-like sheet, a leather-like sheet having a surface having both high resistance to frictional melting and high resistance to bending can be obtained.
[0014] Examples of the spherical fine particles include melamine resin-silica composite particles, benzoguanamine resin particles, and polytetrafluoroethylene resin particles.
[0015] In addition, the surface resin layer preferably has a thickness of 10 to 60 μm from the viewpoint of obtaining a leather-like sheet having a good balance of high friction melting resistance, high bending resistance, and mechanical properties.
[0016] In addition, from the perspective of obtaining a leather-like sheet with an excellent balance between high friction melting resistance and high bending resistance, it is preferred that the cycle for cracks to form in the surface resin layer be 300,000 cycles or more when a bending test is performed using a flex tester at 20°C.
[0017] In addition, from the perspective of obtaining a leather-like sheet having a good balance of high friction melting resistance, high bending resistance and mechanical properties, the fiber base material preferably includes a nonwoven fabric containing ultrafine fibers with a fineness of 0.5 dtex or less and a polymer elastomer impregnated into the nonwoven fabric.
[0018] Effects of the Invention
[0019] According to the present invention, a leather-like sheet having a surface having both high resistance to frictional melting and high resistance to bending can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic cross-sectional view of the leather-like sheet 10 according to the embodiment.
[0021] Explanation of symbols
[0022] 1 Fiber substrate
[0023] 2 Adhesive layer
[0024] 3. Intermediate resin layer
[0025] 4 Surface resin layer
[0026] 5 Grain resin layer
[0027] 4a Spherical particles
[0028] 10 Leather-like pieces DETAILED DESCRIPTION
[0029] Hereinafter, one embodiment of the leather-like sheet of the present invention will be described in detail with reference to the drawings. Figure 1 It is a schematic cross-sectional view of the leather-like sheet 10 of this embodiment.
[0030] Reference Figure 1 The leather-like sheet 10 comprises: a fiber base material 1, an intermediate resin layer 3 bonded to one side of the fiber base material 1 via an adhesive layer 2, and a surface resin layer 4 laminated on the intermediate resin layer 3. The resin layer including the adhesive layer 2, the intermediate resin layer 3 and the surface resin layer 4 forms a grain resin layer (silver-faced resin layer) 5. The grain resin layer 5 is a layer that gives the leather-like sheet 10 a grain-like appearance and touch similar to that of natural leather. The grain resin layer 5 may further include other layers such as an outer coating layer as needed.
[0031] The surface resin layer 4 includes a polymer elastic body containing polyether polyurethane and spherical particles 4a having a heat resistance of 200°C dispersed in the polymer elastic body. The specific heat of the spherical particles 4a is 0.95 kJ / (kg·K) or more, and the particle size D at the cumulative distribution of 50 volume % is 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D 10 ≤3. The surface resin layer 4 contains a high molecular weight elastic body including polyether polyurethane and the above-mentioned spherical fine particles having heat resistance of 200° C., thereby providing the leather-like sheet 10 with a surface having both high friction melting resistance and high bending resistance.
[0032] As the fiber substrate, there can be used without particular limitation: a fiber substrate made of a nonwoven fabric, a woven fabric, a knitted fabric, or a sheet formed by combining these, which is currently used for the production of leather-like sheets and further impregnated with a polymer elastic body as required. Among these, a fiber substrate comprising a nonwoven fabric, particularly a fiber substrate comprising a nonwoven fabric impregnated with a polymer elastic body and containing ultrafine fibers having a fineness of 0.5 dtex or less, is preferred because it is easy to obtain a leather-like sheet that is dense and has high mechanical strength.
[0033] In order to easily obtain a leather-like sheet with low fiber density and high uniformity, it is preferred that the fiber forming the fiber base material contains ultrafine fibers with a fineness of 0.5 dtex or less, and further 0.0001 to 0.2 dtex. It should be noted that the fineness is obtained by photographing a cross section parallel to the thickness direction of the napped artificial leather at 3000 times magnification using a scanning electron microscope (SEM), and calculating the average value based on the diameters of 15 randomly selected fibers and the density of the resin forming the fibers.
[0034] The type of resin forming the fiber is not particularly limited. Specific examples of the resin forming the fiber include: polyamide resins such as polyamide 6, polyamide 66, polyamide 610, aromatic polyamide, and polyamide elastomer; polyester resins such as polyethylene terephthalate (PET), polypropylene terephthalate, polybutylene terephthalate (PBT), and polyester elastomer; acrylic resins; olefin resins; synthetic fibers such as polyvinyl alcohol resins, various natural fibers, and semi-synthetic fibers. These resins can be used alone or in combination of two or more. As a method for manufacturing synthetic fibers, there can be used without particular limitation: a method of melting the resin at a temperature above the melting point and extruding it from an extruder to perform melt spinning; a dry solution spinning method in which a polymer solution can be extruded from a pore to evaporate the solvent; a wet solution spinning method in which a polymer solution is spun in a non-solvent; and the like. In addition, the nonwoven fabric of ultrafine fibers can be obtained by, for example, entangling ultrafine fiber-producing fibers such as sea-island type composite fibers to form a fiber entangling body, and then performing an ultrafine fiberization treatment, and the fiber base material can contain a polymer elastomer impregnated therein. The type of polymer elastomer impregnated into the fiber base material is not particularly limited, and specifically, for example, polyurethane; acrylic elastomers such as acrylonitrile-butadiene copolymers, acrylate or methacrylate copolymers; polyamide elastomers; various polymer elastomers such as silicone rubber. Among these, polyurethane is particularly preferred from the perspective of obtaining a good hand feel. It should be noted that the soft segment of the polyurethane can contain one of a polyester unit, a polyether unit, and a polycarbonate unit, or a combination thereof. In addition, these polymer elastomers can be used alone or in combination of two or more.
[0035] When the fiber base material contains an elastic polymer impregnated therein, the mass ratio of the fiber forming the fiber base material to the elastic polymer (fiber / elastic polymer) is preferably in the range of 50 / 50 to 100 / 0, more preferably 60 / 40 to 95 / 5. When the elastic polymer content is too high, the obtained leather-like sheet tends to have a hard feel like rubber.
[0036] The thickness of the fiber substrate is not particularly limited, but is preferably 0.3 to 2.0 mm, more preferably 0.5 to 1.5 mm.
[0037] Reference Figure 1 A surface resin layer 4 is laminated on one side of a fiber base material 1 of a leather-like sheet 10 via an adhesive layer 2 and an intermediate resin layer 3. The surface resin layer 4 is a layer that gives the surface of the leather-like sheet a high resistance to friction melting when the surface is repeatedly rubbed, and a high resistance to bending such as not easily cracking even after repeated bending. Such a surface resin layer 4 includes a polymer elastic body containing polyether polyurethane, and spherical particles 4a having a heat resistance of 200°C dispersed in the polymer elastic body.
[0038] The spherical particles have a heat resistance of 200°C, a specific heat of 0.95 kJ / (kg·K) or more, and have the following particle size distribution: the particle size D at 50% by volume of the cumulative distribution is 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D 10 ≤3.
[0039] Spherical particles having heat resistance at 200° C. are particles that do not melt when heated for 10 minutes in a dryer set at 200° C. as described later. If the spherical particles do not have heat resistance at 200° C., frictional melting resistance decreases.
[0040] In addition, as described later, the spherical particles satisfying the specific heat of 0.95 kJ / (kg·K) or more are based on JIS K7123: Method for Determining Specific Heat Capacity of Plastics and the specific heat of the spherical particles is measured by the DSC (differential scanning calorimeter) method. The specific heat of the spherical particles is 0.95 kJ / (kg·K) or more, and more preferably 1.00 kJ / (kg·K) or more. When the specific heat of the spherical particles is less than 0.95 kJ / (kg·K), the frictional melting resistance is reduced. By making the specific heat 0.95 kJ / (kg·K) or more, the rate at which the temperature of the surface resin layer containing the spherical particles rises due to frictional heat is suppressed.
[0041] As specific examples of spherical particles having a heat resistance of 200°C and a specific heat of 0.95 kJ / (kg·K) or more, there can be cited, for example, melamine resin-silica composite particles, benzoguanamine resin particles, polytetrafluoroethylene (PTFE) resin particles, etc. These particles are preferably cross-linked spherical resin particles. It should be noted that, although "spherical" does not necessarily mean a sphere, it is at least not a particle produced by crushing like a sheet. Among these, melamine resin-silica composite particles are particularly preferred because of the presence of silica on the surface of the particles, and the particles are not easy to fuse to each other even if the temperature exceeds 200°C.
[0042] Furthermore, the particle size D at 50% by volume of the cumulative distribution of spherical particles is 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D 10 ≤3. The spherical fine particles having heat resistance of 200° C. and a specific heat of 0.95 kJ / (kg·K) or more have improved frictional melting resistance by having such a controlled particle size and a narrow particle size dispersion.
[0043] Spherical particle size D 50 (Median particle size) is 2.5 to 10 μm. 50 When the particle size D exceeds 10 μm, the surface of the surface resin layer becomes rough, the wear resistance is easily reduced, or the appearance quality is easily reduced due to the observation of coarse particles. In addition, when the surface resin layer is formed by coating, linear unevenness is easily formed on the surface. 50 If the particle size is less than 2.5 μm, the proportion of fine particles that contribute little to the improvement of frictional fusion resistance increases, and therefore, it is difficult to obtain a sufficient effect.
[0044] In addition, spherical particles satisfy the particle size dispersion D 50 / D 10 ≤3, and the particles are controlled to have a narrow particle size distribution. When the particle size dispersion of the spherical particles is D 50 / D 10 >3, the particle size is D 10 The proportion of the following particles is relatively high. 10 The following fine particles contribute little to the improvement of frictional melting resistance. Therefore, in order to obtain high frictional melting resistance, the blending ratio of spherical fine particles must be increased. In this case, the bending resistance is likely to decrease.
[0045] The surface resin layer contains a high molecular weight elastic body including polyether polyurethane.
[0046] The polyether polyurethane is obtained by reacting a polymer polyol containing a polyether polyol, an organic polyisocyanate, and a urethane raw material containing a chain extender.
[0047] Specific examples of the polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, and poly(methyltetramethylene glycol).
[0048] Specific examples of organic polyisocyanates include: diisocyanates that are difficult to yellow including aromatic diisocyanates such as 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; non-yellowing diisocyanates such as aliphatic or alicyclic diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, norbornene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate; and the like.
[0049] Specific examples of chain extenders include diamines such as hydrazine, ethylenediamine, propylenediamine, hexamethylenediamine, nonamethylenediamine, xylylenediamine, isophoronediamine, piperazine and its derivatives, adipic acid dihydrazide, and isophthalic acid dihydrazide; triamines such as diethylenetriamine; tetraamines such as triethylenetetramine; diols such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-bis(β-hydroxyethoxy)benzene, and 1,4-cyclohexanediol; triols such as trimethylolpropane; tetraols such as pentaerythritol; amino alcohols such as aminoethanol and aminopropanol, and the like.
[0050] As the ratio of the polyether polyurethane contained in the polymer elastomer included in the surface resin layer, it is preferably 60% by mass or more, more preferably 80% by mass or more, and particularly preferably 90 to 100% by mass from the aspect of easily maintaining particularly high bending resistance. As the polymer elastomer other than the polyether polyurethane contained in the polymer elastomer, polyurethane other than polyether polyurethane such as polyester polyurethane and polycarbonate polyurethane, acrylic elastomers such as acrylonitrile-butadiene copolymer, acrylate or methacrylate copolymer, polyamide elastomer, various polymer elastomers such as silicone rubber can be cited. In addition, as the ratio of the polyether polyurethane contained in the surface resin layer, it is preferably 40% by mass or more, more preferably 50% by mass or more, and particularly preferably 60% by mass or more.
[0051] In addition, the content of the spherical particles in the surface resin layer is 5 to 40% by mass. When the content of the spherical particles in the surface resin layer is less than 5% by mass, the frictional melting resistance cannot be fully improved. In addition, when the content of the spherical particles in the surface resin layer exceeds 40% by mass, the bending resistance is easily reduced.
[0052] The surface resin layer may contain various additives such as antioxidants, ultraviolet absorbers, pigments, dyes, surfactants, antistatic agents, flame retardants, release agents, fillers, crosslinking agents, etc. as necessary, unless the effects of the present invention are impaired.
[0053] The thickness of the surface resin layer is preferably 10 to 60 μm, more preferably 15 to 45 μm, from the viewpoint of easily obtaining a leather-like sheet having a surface having high friction melting resistance, high bending resistance, and a soft feel like natural leather.
[0054] Reference Figure 1 , the surface resin layer 4 is laminated on the fiber base material 1 via the adhesive layer 2 and the intermediate resin layer 3. The leather-like sheet of the present embodiment can be manufactured, for example, by the following method: forming a surface resin layer on a release paper, further forming an intermediate resin layer on the surface of the surface resin layer, forming an adhesive layer on the surface of the intermediate resin layer, and after the adhesive layer formed on the release paper is pressed and bonded to the surface of the fiber base material, the release paper is peeled off.
[0055] The intermediate resin layer is a layer mainly composed of a polymer elastomer, and contains various additives such as antioxidants, ultraviolet absorbers, pigments, dyes, surfactants, antistatic agents, flame retardants, anti-adhesive agents, fillers, crosslinking agents, etc. as needed. The type of polymer elastomer forming the intermediate resin layer is not particularly limited, and examples thereof include: polyurethane; acrylic elastomers such as acrylonitrile-butadiene copolymers, acrylate or methacrylate copolymers; polyamide elastomers; various polymer elastomers such as silicone rubber. Among these, polyurethane is preferred from the perspective of obtaining a good hand feel, and polyether polyurethane is particularly preferred from the perspective of easily improving bending resistance.
[0056] The thickness of the intermediate resin layer is not particularly limited, but is preferably 10 to 60 μm, more preferably 15 to 45 μm, from the viewpoint of easily obtaining a leather-like sheet having an excellent balance between mechanical properties and texture.
[0057] In addition, the adhesive layer is also a layer with a polymer elastic body as the main body, and contains various additives such as antioxidants, ultraviolet absorbers, pigments, dyes, surfactants, antistatic agents, flame retardants, antitackifiers, fillers, crosslinking agents, etc. as required. The type of the polymer elastic body forming the adhesive layer is not particularly limited, and an adhesive containing various polymer elastic bodies similar to the above and a fiber substrate and a polymer elastic body with high adhesion as the main body can be used without special restrictions. As the polymer elastic body that becomes the main body of the adhesive layer, polyurethane is preferred from the aspect of being able to obtain a good feel, and polyether polyurethane is preferred from the aspect of being easy to improve the bending resistance.
[0058] The thickness of the adhesive layer is not particularly limited, but is preferably 20 to 100 μm, more preferably 30 to 90 μm, from the viewpoint of easily obtaining a leather-like sheet having an excellent balance between mechanical properties and texture.
[0059] The leather-like sheet of the present embodiment described above has both high resistance to frictional melting and high resistance to bending. In particular, a leather-like sheet can be obtained in which cracks are generated in the surface resin layer in a bending test using a flexure tester at 20°C for more than 300,000 cycles, and further more than 500,000 cycles.
[0060] Example
[0061] Next, the present invention will be described in more detail by way of examples, but the scope of the present invention is not limited by the following examples. First, the evaluation methods used in the present examples will be summarized and described below.
[0062] (1) Heat resistance of spherical particles at 200°C
[0063] 2 to 3 g of the powder of the spherical particles used in each example was weighed into an aluminum foil container and heated in an electric drying machine at 200°C for 10 minutes. Then, the following cases were judged as A (with 200°C heat resistance): the spherical particles remained in powder form after cooling, or they were slightly sticky but dispersed and returned to powder by applying a slight force with a medicine spoon, etc. In addition, the following cases were judged as B (without 200°C heat resistance): the particles melted and formed into a film, or the particles were completely fused to each other and did not return to powder even if a slight force was applied.
[0064] (2) Determination of particle size and particle size dispersion of spherical particles
[0065] The cumulative particle size distribution of the spherical particles used in each example was measured by a dry method using a laser diffraction scattering measuring device LA-950V2 (Horiba, Ltd.). Then, based on the measured cumulative particle size distribution, the particle size at which the cumulative distribution is 50% by volume is set as D 50 The particle size at the cumulative distribution of 10 volume % is defined as D 10 , calculate the particle size dispersion D 50 / D 10 .
[0066] (3) Specific heat of spherical particles
[0067] The specific heat (kJ / (kg·K)) of the spherical fine particles used in each example was measured using a differential scanning calorimeter DSC8500 (Perkin Elmer) in accordance with JIS K 7123: Method for measuring specific heat capacity of plastics.
[0068] (4) Frictional melting resistance
[0069] A long strip test piece (3×6 cm) was cut from the leather-like sheet obtained in each example. Then, a cherry roll (73 mm in diameter, 26 mm in width) rotating at 1800 rpm was brought into contact with the side of the long strip test piece on which the surface resin layer was formed under a load of 2.0 lb (907 g). Then, the time until the surface resin layer melted and the fiber substrate was exposed was measured at intervals of 1 second (rounded off), and the maximum measurement was up to 10 seconds.
[0070] (5) Bending resistance
[0071] The bending resistance test of the leather-like sheets obtained in each example was carried out using a flexure tester in accordance with JIS K6545 in an environment of relative humidity 65±5% and temperature 20±2°C. Specifically, the flexure tester was used to confirm whether cracks were generated on one side of the leather-like sheet on which the surface resin layer was formed every 100,000 bending cycles. The cracks were confirmed by visual observation using a 30x magnifying glass. Then, when cracks were confirmed in 100,000 cycles, it was judged as "less than 100,000 cycles", and when cracks were confirmed in 200,000 cycles, it was judged as "100,000 cycles", and the others were similarly judged every "100,000 cycles". It should be noted that in each cycle, the number of samples was N=3. Then, when cracks were generated in any of the samples, it was judged as cracks.
[0072] [Example 1]
[0073] Water-soluble thermoplastic polyvinyl alcohol was used as the sea component, PET with an isophthalic acid modification degree of 6 mol% was used as the island component, and a melt composite spinning nozzle was used in which the number of islands per fiber was 25 and the sea component / island component was 25 / 75 (mass ratio). The filaments of the sea-island composite fiber were ejected from the nozzle at 260°C. Then, the ejector pressure was adjusted so that the spinning speed was 4000m / min, and the sea-island composite fiber with an average fineness of 2.5dtex was captured on a net to obtain a fiber with a unit area weight of 30g / m 2 A web of long fibers.
[0074] Then, the net was cross-laid to form 12 layers, and a needle-breaking prevention oil was sprayed on it. Then, a 6-hook needle was used at 2000 pricks / cm 2 The material is needle punched with a needle punching density of , thereby obtaining a bonded mesh.
[0075] Then, the entangled web was passed through water vapor to be heat shrunk. Specifically, first, 30% by mass of water relative to the mass of the sea component was added to the entangled web, and then heat treated for 80 seconds in a heated water vapor atmosphere at a relative humidity of 90% and a temperature of 110°C. The area shrinkage at this time was 45%.
[0076] Next, the heat-shrunk web was impregnated with a dispersion of anionic self-emulsifying aqueous polyurethane (100% modulus 3.0 MPa). It should be noted that the concentration of the aqueous polyurethane dispersion was such that the mass ratio of the aqueous polyurethane / island component was 10 / 90. Then, the aqueous polyurethane dispersion was gelled in a water vapor atmosphere to prevent migration, and then dried at 120°C for 10 minutes.
[0077] Then, the web impregnated with aqueous polyurethane was immersed in hot water at 95°C for 10 minutes to remove the sea component and form ultrafine fibers. Then, by drying at 120°C for 10 minutes, a fiber substrate with a thickness of 2.1 mm of nonwoven fabric containing ultrafine fibers of 0.1 dtex was obtained. Then, by slicing the fiber substrate with a thickness of 2.1 mm on a surface roughly parallel to its surface, a nonwoven fabric with a thickness of 1.0 mm and a unit weight of 525 g / m2 containing ultrafine fibers of 0.1 dtex was obtained. 2 fiber substrate.
[0078] Then, a roll coater was used to apply the wet coating at a weight of 130 g / m 2 A coating liquid for forming a surface resin layer is applied to the pore-shaped release paper and dried. The coating liquid is prepared by mixing 100 parts by mass of polyether polyurethane (Pet PU, Resamine ME-8116 manufactured by Dainichi Seika Industries Co., Ltd., with a solid content of 30% by mass), 8.5 parts by mass of melamine resin-silicon dioxide composite particles (Optbeads 6500M manufactured by Nissan Chemical Industries Co., Ltd.), 30 parts by mass of DMF, 10 parts by mass of MEK, and 30 parts by mass of black pigment dispersion (DUT-4794 manufactured by Dainichi Seika Industries Co., Ltd., with a pigment content of 12% by mass). Thus, a surface resin layer is formed. The formed surface resin layer contains 20% by mass of melamine resin-silicon dioxide composite particles.
[0079] Next, a roll coater was used to apply the wet coating at a weight of 105 g / m 2 A coating liquid for forming an intermediate resin layer was applied to the surface of the surface resin layer and then dried. The coating liquid was prepared by mixing 100 parts by mass of a polyether polyurethane (Resamine ME-8116 manufactured by Dainichi Seika Industries Co., Ltd., solid content 30% by mass), 30 parts by mass of DMF, 10 parts by mass of methyl ethyl ketone, and 30 parts by mass of a black pigment dispersion (DUT-4794 manufactured by Dainichi Seika Industries Co., Ltd.: pigment content 12% by mass). Thus, an intermediate resin layer was formed.
[0080] Then, a roll coater was used to apply the wet coating amount of 150 g / m 2The surface of the intermediate resin layer was coated with a coating liquid for forming an adhesive layer, the coating liquid being prepared by blending 100 parts by mass of a polyether polyurethane (Resamine UD-8310NTT manufactured by Dainichi Seika Industries Co., Ltd., solid content 60% by mass), 10 parts by mass of an isocyanate crosslinking agent (NE crosslinking agent manufactured by Dainichi Seika Industries Co., Ltd.), 2 parts by mass of a crosslinking accelerator (UD-103 manufactured by Dainichi Seika Industries Co., Ltd.), 30 parts by mass of DMF, and 20 parts by mass of MEK, and then dried at 80°C for 2 minutes, adhered to the surface of the fiber substrate in a semi-dried state, and further dried at 130°C for 5 minutes. Then, in order to promote the crosslinking reaction of the adhesive layer, it was heated in a dryer at an atmospheric temperature of 60°C for 48 hours. Then, the release paper was peeled off to expose the surface resin layer.
[0081] Thus, a leather-like sheet with a thickness of about 1 mm was obtained. The cross section of the obtained leather-like sheet was observed by a scanning electron microscope (300 times), and the film thickness of 30 randomly selected positions was measured to obtain the average value. The thickness of the surface resin layer was 30 μm, the thickness of the intermediate resin layer was 30 μm, and the thickness of the adhesive layer was 60 μm.
[0082] Then, the properties of the obtained leather-like sheet were evaluated by the above-mentioned evaluation method. The evaluation results are shown in Table 1.
[0083]
[0084] [Example 2]
[0085] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1, except that benzoguanamine resin particles (Epostar M05, manufactured by Nippon Shokubai Co., Ltd.) were added to the surface resin layer instead of melamine resin-silica composite particles (Optbeads 6500M, manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0086] [Example 3]
[0087] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the surface resin layer contained 5 mass % of melamine resin-silica composite particles instead of 20 mass % of melamine resin-silica composite particles.
[0088] [Example 4]
[0089] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the surface resin layer contained 40% by mass of melamine resin-silica composite particles instead of 20% by mass of melamine resin-silica composite particles. The results are shown in Table 1.
[0090] [Example 5]
[0091] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that PTFE particles (Microdispers-3000, manufactured by Polysciences) were added to the surface resin layer instead of melamine resin-silica composite particles (Optbeads6500M, manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0092] [Example 6]
[0093] The results are shown in Table 1. A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the film thickness of the surface resin layer was changed from 30 μm to 60 μm.
[0094] [Example 7]
[0095] The results are shown in Table 1. A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the film thickness of the surface resin layer was changed from 30 μm to 80 μm.
[0096] [Comparative Example 1]
[0097] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that melamine resin-silica composite particles (Optbeads 6500M, manufactured by Nissan Chemical Industries, Ltd.) were not blended in the surface resin layer.
[0098] [Comparative Example 2]
[0099] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1 except that melamine resin particles (manufactured by Huber Engineered Materials, PERGOPAK M4) were blended in the surface resin layer instead of melamine resin-silica composite particles (manufactured by Nissan Chemical Industries, Ltd., Optbeads 6500M). The results are shown in Table 1.
[0100] [Comparative Example 3]
[0101] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the surface resin layer contained 3 mass % of melamine resin-silica composite particles instead of 20 mass % of melamine resin-silica composite particles.
[0102] [Comparative Example 4]
[0103] A leather-like sheet was produced and evaluated in the same manner as in Example 1 except that the surface resin layer contained 50% by mass of melamine resin-silica composite particles instead of 20% by mass of melamine resin-silica composite particles. The results are shown in Table 1.
[0104] [Comparative Example 5]
[0105] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1, except that polymethyl methacrylate (PMMA) resin particles (Taftic AR650SX, manufactured by Nippon EXLAN Industries, Ltd.) were added to the surface resin layer instead of melamine resin-silica composite particles (Optbeads 6500M, manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0106] [Comparative Example 6]
[0107] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1, except that aluminum flakes (TS-408PM manufactured by Toyo Aluminum Co., Ltd.) were added to the surface resin layer instead of melamine resin-silica composite particles (Optbeads 6500M manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0108] [Comparative Example 7]
[0109] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1, except that 100 parts by mass of polycarbonate polyurethane (PC PU, Resamine ME-8210NS manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) was added to the surface resin layer instead of 100 parts by mass of polyether polyurethane (Resamine ME-8116 manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) as the polymer elastic body to be added. The results are shown in Table 1.
[0110] [Comparative Example 8]
[0111] In Example 1, a leather-like sheet was produced in the same manner as in Example 1, and evaluated, except that 100 parts by mass of polycarbonate polyurethane (Resamine ME-8210NS manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) was added to the surface resin layer instead of 100 parts by mass of polyether polyurethane (Resamine ME-8116 manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) as the polymer elastic body to be added, and 33% by mass of benzoguanamine resin particles (Epostar MS manufactured by Nippon Shokubai Co., Ltd.) were added instead of 20% by mass of melamine resin-silica composite particles (Optbeads 6500M manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0112] [Comparative Example 9]
[0113] In Example 1, a leather-like sheet was produced in the same manner as in Example 1, except that 100 parts by mass of polycarbonate polyurethane (Resamine ME-8210NS manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) was added to the surface resin layer instead of 100 parts by mass of polyether polyurethane (Resamine ME-8116 manufactured by Dainichi Seika Industries, Ltd., solid content 30% by mass) as the polymer elastic body to be added, and 50% by mass of melamine resin particles (Epostar S12 manufactured by Nippon Shokubai Co., Ltd.) were added instead of 20% by mass of melamine resin-silica composite particles (Optbeads 6500M manufactured by Nissan Chemical Industries, Ltd.). The results are shown in Table 1.
[0114] [Comparative Example 10]
[0115] In Example 1, a leather-like sheet was produced and evaluated in the same manner as in Example 1, except that melamine resin-silica composite particles (manufactured by Nissan Chemical Industries, Ltd., Optbeads 10500M) were blended in the surface resin layer instead of melamine resin-silica composite particles (manufactured by Nissan Chemical Industries, Ltd., Optbeads 6500M). The results are shown in Table 1.
[0116] Referring to Table 1, there are spherical particles containing polyether polyurethane and having heat resistance at 200°C, the content ratio of the spherical particles is 5 to 40% by mass, the specific heat of the spherical particles is 0.95 kJ / (kg·K) or more, and the particle size D when the cumulative distribution is 50% by volume 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D10 The leather-like sheets obtained in Examples 1 to 7 with a surface resin layer having a particle size distribution of ≤3 all had a friction melting resistance of more than 5 seconds and a bending resistance of more than 300,000 times. On the other hand, the leather-like sheet of Comparative Example 1 having a surface resin layer without spherical particles had a friction melting resistance of less than 1 second. 50 / D 10 The leather-like sheet of Comparative Example 2 having a surface resin layer of spherical particles with a specific heat of less than 3 has a friction melting resistance of 2 seconds. In addition, the leather-like sheet of Comparative Example 3 having a surface resin layer containing 3 mass% of spherical particles has a friction melting resistance of 1 second. In addition, the leather-like sheet of Comparative Example 4 having a surface resin layer containing 50 mass% of spherical particles has a bending resistance of less than 100,000 times. In addition, the leather-like sheet of Comparative Example 5 having a surface resin layer containing PMMA particles that are spherical particles that do not have heat resistance of 200°C has a friction melting resistance of less than 1 second. In addition, the leather-like sheet of Comparative Example 6 having a surface resin layer containing aluminum flakes having a specific heat of less than 0.95 kJ / (kg·K) has a friction melting resistance of less than 1 second. In addition, the leather-like sheets of Comparative Examples 7 to 9 having a surface resin layer containing polycarbonate polyurethane all have a bending resistance of less than 100,000 times. In addition, D 50 The leather-like sheet of Comparative Example 10 having a particle size exceeding 10 μm had a bending resistance of 100,000 times. In addition, when the particles were applied using a roll coater, stripe-like irregularities were formed on the surface of the coating film.
Claims
1. A leather-like sheet comprising: a fiber base material, an intermediate resin layer laminated on one side of the fiber base material, and a surface resin layer laminated on the intermediate resin layer, wherein: The surface resin layer contains a high molecular weight elastic body and spherical particles having a heat resistance of 200°C. The spherical particles are at least one selected from melamine resin-silicon dioxide composite particles and benzoguanamine resin particles. 90 to 100% by mass of the polymer elastic body in the surface resin layer is polyether polyurethane. The content ratio of the spherical fine particles in the surface resin layer is 5 to 40% by mass. The specific heat of the spherical particles is 1.00 kJ / (kg·K) or more, and the particle size D when the cumulative distribution is 50% by volume 50 (Median diameter) is 2.5 to 10 μm, and the particle size D when the cumulative distribution is 10% by volume 10 Meet the particle size dispersion D 50 / D 10 ≤3.
2. The leather-like sheet according to claim 1, wherein The surface resin layer has a thickness of 10 to 60 μm.
3. The leather-like sheet according to claim 1 or 2, wherein: When a bendability test was conducted using a flex tester in an environment of 20° C., the number of cycles required for cracks to form in the surface resin layer was 300,000 cycles or more.
4. The leather-like sheet according to claim 1 or 2, wherein: The fiber substrate includes a nonwoven fabric containing ultrafine fibers having a fineness of 0.5 dtex or less, and a polymer elastic body impregnated into the nonwoven fabric.
